This is not a drill: towards a sonic and sensorial musicriminology - Lee, Murray (Crime, media, culture, 2022)
The first half of this article makes that case for, and develops, a preliminary conceptual framework for a ‘musicriminology’. A response to recent provocations for a more sensorially orientated criminology, and more general appeals for cultural criminology to engage rigorously with popular music and sound, a musicriminology could constitute significant contribution to the cultural criminological field. The article proposes two key conceptual themes, culture and co-production that underpin such a framework. Into these broad (Double-C) themes are incorporated theories of the cultural, material, aesthetics, sonics, and the sensorial. The second half of the article uses drill music, a subset of rap or hip-hop music, as a case study. The focus is on the popular western Sydney drill group OneFour, who have recently been subject to police attempts to suppress them on the basis that their lyrics ‘incite violence’. With dark, nihilistic and sometimes violent lyrics typically narrating street life, drill is often characterised by performers’ relationship to place-groups are sometimes even named after their postcode. In the United States, the United Kingdom, and Australia drill music has attracted the attention of police, politicians, and mainstream media for artists’ alleged relationship to street-based violence. The article suggests that OneFour’s music challenges an accepted aesthetic and cultural order. However, somewhat ironically the group has become more popular as a result of police attempts to criminalise them and to re-assert such an order.